Grandfather Clause in the Trade Sector as a Security in Investment after Job Creation Act - Fitriyani, Anisa Hesti; Dirkareshza, Rianda (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2021)
This study discusses the application of the Grandfather Clause, especially in the trade sector, as a form of certainty in investment law after the issuance of the Job Creation Act. The main issues discussed in this study are how to apply the Grandfather Clause to ensure legal certainty for investors and business actors in the trade sector pre-Job Creation Act. And whether the Grandfather Clause can be a form of legal certainty for investors and business actors in the trade sector that engaged in the post-Job Creation Act. Of course, the aim is to analyze the application of the Grandfather Clause, especially in the trade sector, as a means of legal certainty for investors or business actors engaged in the trading sector. The research method used is a normative research method with a statute approach. The research results show that implementing the Grandfather Clause after changes of the Negative Investment List (DNI) from year to year can provide legal certainty for investors and business actors. In addition, it is also known that the actual implementation of the Grandfather Clause can be adjusted according to the preferences of investors and business actors. In this case, the Grandfather Clause may not be applied if it is felt that the provisions and licensing requirements in the existing regulations are considered more profitable.